Accident or suicide? Improvement in the classification of suicides among road traffic fatalities in Sweden by extended psychosocial investigations, during the years 2010–2019. (February 2022) - Andersson, Anna-Lena; Sokolowski, Marcus
Highlights: Suicides are difficult to distinguish from accidents among road traffic fatalities. Psychosocial investigations helped to identify more suicides. Psychosocial investigations helped to resolve many "undetermined" causes of death. The improved classification will help prevention of suicide deaths in road traffic. Abstract: Introduction: Suicide is the second leading cause of death in the ages 15–29 worldwide, exceeded only by road injury. However, fatalities in road traffic may be either accidents or suicides. In 2010 Sweden began efforts to separately report deaths in road traffic as either accidents or suicides. Method: Three alternative criteria defining what constitutes a fatality by suicide were introduced. After exclusion of natural deaths, fatalities were also classified on a five-level graded scale, which distinguished between accident, undetermined, and suicide. The investigations of fatalities were complemented by extended psychosocial investigations in 2012. The improvement in the classification of suicide deaths was evaluated by an intra-year 2012 comparison, as well as using the 2010–2012 period as a control to evaluate the continued use of extended psychosocial investigations during the 2013–2019 period. Results: The 2012 intra-year comparison showed a 63% increase in the number of identified suicides when using extended psychosocial investigations. The additional 14 suicides identified in 2012 were mainly attributed to a resolution of 12 "undetermined" causes of deaths. Suicides of all road fatalities increased from 5.7-6.8% in 2010–2011, to 11.2% in 2012. Over the subsequent period 2013–2019 with extended psychosocial investigations, suicides of all road fatalities averaged 10%, a 60% increase over prior years. An average of ∼9 additional suicides was identified each year during 2013–2019, which was accompanied by an annual reduction of ∼6 "undetermined" fatalities. Conclusion: The use of extended psychosocial investigations is of major importance for our knowledge about the occurrence of suicides in road traffic. Practical applications: A standardized and in-depth classification of suicide deaths is a basic prerequisite needed for the cooperation, implementation, and effect-evaluations of suicide intervention and prevention efforts, with potential to include the entire Swedish transportation system.